Novel coumarins active against Trypanosoma cruzi and toxicity assessment using the animal model Caenorhabditis elegans - Fabiana Gomes Nascimento Soares; Gabriela Göethel; Luciano Porto Kagami; Gustavo Machado das Neves; Elisa Sauer; Estefania Birriel; Javier Varela; Itamar Luís Gonçalves; Gilsane Von Poser; Mercedes González; Daniel Fábio Kawano; Fávero Reisdorfer Paula; et al. (BMC, 2019)
Abstract Background Chagas disease (CD) is a tropical parasitic disease. Although the number of people infected is very high, the only drugs available to treat CD, nifurtimox (Nfx) and benznidazole, are highly toxic, particularly in the chronic stage of the disease. Coumarins are a large class of compounds that display a wide range of interesting biological properties, such as antiparasitic. Hence, the aim of this work is to find a good antitrypanosomal drug with less toxicity. The use of simple organism models has become increasingly attractive for planning and simplifying efficient drug discovery. Within these models, Caenorhabditis elegans has emerged as a convenient and versatile tool with significant advantages for the toxicological potential identification for new compounds. Methods Trypanocidal activity: Forty-two 4-methylamino-coumarins were assayed against the epimastigote form of Trypanosoma cruzi (Tulahuen 2 strain) by inhibitory concentration 50% (IC50). Toxicity assays: Lethal dose 50% (LD50) and Body Area were determined by Caenorhabditis elegans N2 strain (wild type) after acute exposure. Structure-activity relationship: A classificatory model was built using 3D descriptors. Results Two of these coumarins demonstrated near equipotency to Nifurtimox (IC50 = 5.0 ± 1 μM), with values of: 11 h (LaSOM 266), (IC50 = 6.4 ± 1 μM) and 11 g (LaSOM 231), (IC50 = 8.2 ± 2.3 μM). In C. elegans it was possible to observe that Nfx showed greater toxicity in both the LD50 assay and the evaluation of the development of worms. It is possible to observe that the efficacy between Nfx and the synthesized compounds (11 h and 11 g) are similar. On the other hand, the toxicity of Nfx is approximately three times higher than that of the compounds. Results from the QSAR-3D study indicate that the volume and hydrophobicity of the substituents have a significant impact on the trypanocidal activities for derivatives that cause more than 50% of inhibition. These results show that the C. elegans model is efficient for screening potentially toxic compounds. Conclusion Two coumarins (11 h and 11 g) showed activity against T. cruzi epimastigote similar to Nifurtimox, however with lower toxicity in both LD50 and development of C. elegans assays. These two compounds may be a feasible starting point for the development of new trypanocidal drugs.